Water Security as Shared Security Challenges? A Comparison of Kazakhstan and Uzbekistan Security Discourse towards the Aral Sea - Radityo Dharmaputra (Global Strategis, 2015)
This article analyses the water security problems in Central Asia bycomparing Kazakhstan’s and Uzbekistan’s policy regarding the Aral Sea. Asone of the perpetual problem in Central Asia, the condition of freshwaterresources in the Aral Sea has been worsening for the last decades. Efforts bygovernments were isolated and unorganised. Both the Kazakhstan and theUzbek government, which had their own share of the problem, had beenunable to cooperate on this issue. This article tries to elaborate the problem by using the theory on securitisation process, regional security complex, and the patterns of amity-enmity. This research finds that while the amity-enmitypatterns was absent, the differing process of securitisation (in Kazakhstan)and de-securitisation (in Uzbekistan) had forced both states to embark on their own strategies and policies regarding the Aral Sea.